Defending the African philosophy of ubuntu and its place in clinical social work practice in mental health: the biopsychosocial and ecological systems perspectives - Chigangaidze, Robert K. (Routledge, 2022)
While other scholars argue that there seems to be a disjuncture when it comes to applying ubuntu in clinical social work, the impetus of this discourse is to reflect on ubuntu as a philosophy applicable to clinical social work interventions in mental health. Assuming that clinical social work is based on the biopsychosocial and ecological models, it explores how ubuntu is relevant in the assessment, diagnosis, treatment, and prevention of behavioral, emotional, and mental disorders. The article calls for the adoption of ubuntu philosophy to the theoretical framework of clinical social work practice in mental health.